MONITOR AND CONTROL-BASED RASPBERRY PI FOR DESIGNING SMART HOME THROUGH INTERNET OF THINGS - Dodi Yudo Setyawan; Heri Setiawan (Proceeding International Conference on Information Technology and Business, 2020)
Almost all service devices were connected to the internet in this modern era. They were in the form of a form of rapid technological development and advancement. The type of this technology was known as Internet of Things (IoT) that was able to be embedded in smart home systems. Sensor and actuator devices that were implemented in the house were able to be controlled through the android application. The objective of this study was to develop the accuracy of monitoring and controlling the home electronic equipments through the controlled device using sensors to generate a status as a sign. The result of this study was that the controlled device status was able to generate feedback data to the Android so that the device was on or off. The average time to obtain the feedback was 4 seconds.Keywords:Internet of Things, Smart Home, Controlling, Monitoring.